Effect of short-term failure versus nonfailure training on lower body muscular endurance - Willardson, J. M.; Emmett, J.; Oliver, J. A.; Bressel, E. (International Journal of Sports Physiology and Performance, 2008)
Purpose: This study compared failure versus nonfailure training with equated intensity and volume on lower body muscular endurance in trained men. Methods: Each subject performed one lower body workout per week for 6 weeks; the Failure group performed 3 sets of the squat, leg curl, and leg extension exercises to the point of voluntary exhaustion, while the Nonfailure group performed 4 sets for each of these exercises, but with a submaximal number of repetitions that did not allow failure to occur on any set. All subjects performed a pre- and postintervention muscular endurance test that involved 3 sets each for the squat, leg curl, and leg extension exercises. Blood lactate concentration (BL) was assessed before, and at 5 and 10 minutes following the test. Heart rate (HR) was assessed before the test, following the last set of each exercise, and for 10 minutes following the test. Results: Both groups demonstrated significant increases in total work (P < .0001) for the postintervention test, with no significant differences between the groups (P = .882). When comparing the pre- and postintervention tests, BL and HR were not significantly different at any time point (P > .05). Conclusions: These results indicate that when intensity and volume are equated, failure or nonfailure training results in similar gains in lower body muscular endurance. Therefore, when assessed over relatively short training cycles, the total volume of training might be more important versus whether sets are performed to failure for muscular endurance-related adaptations.